2011
DOI: 10.1590/s0006-87052011000400030
|View full text |Cite
|
Sign up to set email alerts
|

Coffee crop coefficient for precision irrigation based on leaf area index

Abstract: Crop coefficient (Kc) for coffee plantations was found to be linearly related to the leaf area index (L) up to 3, i.e., Kc = b L. The basic assumption is that for irrigated trees the water use per unit leaf area (ET LA) is equal to the reference evapotranspiration (ETo) expressed also on a unit leaf area basis of the reference surface (ET LA = ETo/Lo). As recommended by FAO-56 the leaf area index (Lo) for the hypothetical reference surface (grass) is equal to 2.88, then the most likely value is b = Lo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
4
5
0
1
Order By: Relevance
“…The Kc values obtained in this study are consistent with those found in the literature for coffee crops (Doorenbos & Pruitt, 1977;Allen et al, 1998;Villa Nova et al, 2002;Marin et al, 2005;Oliveira et al, 2007;Sato et al, 2007;Pereira et al, 2011;Flumignan et al, 2011).…”
Section: Variabsupporting
confidence: 91%
See 3 more Smart Citations
“…The Kc values obtained in this study are consistent with those found in the literature for coffee crops (Doorenbos & Pruitt, 1977;Allen et al, 1998;Villa Nova et al, 2002;Marin et al, 2005;Oliveira et al, 2007;Sato et al, 2007;Pereira et al, 2011;Flumignan et al, 2011).…”
Section: Variabsupporting
confidence: 91%
“…The studies published of Kc in irrigated coffee include those of Flumignan et al 2011, Marin et al (2005), Oliveira et al (2007), Pereira et al (2011) and others related with cultural practices or growth of the culture carried out and published by Villa Nova et al 2002and Sato et al (2007).…”
Section: Variabmentioning
confidence: 99%
See 2 more Smart Citations
“…Por su parte la ET c expresa la evapotranspiración de un cultivo que se desarrolla libre de enfermedades, con buena fertilización, que crece en un campo extenso bajo condiciones óptimas de humedad en el suelo y alcanza su producción total bajo ciertas condiciones climáticas (FAO, 2006). El cálculo de la ET c se representa en la ecuación 4 (Casa et al, 2000;Pereira et al, 2011).…”
Section: Evapotranspiración Del Cultivo: Et Cunclassified